SDG 13: HOW CAN AGRICULTURE TACKLE CLIMATE CHANGE EFFECTS IN THE BAHAMAS AND THE CARIBBEAN? - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2021)
Dr. Víctor Falguera, Ingeniero Agrónomo y Co-Fundador de AKIS International y E-STRATOS Geosystems Spain